Korelasi Interaksi Sosial dan Kemandirian Activity of Daily Living dengan Tingkat Depresi pada Lansia di Panti Sosial - Mutia Shofa; Iskim Luthfa; Moch. Aspihan (Journal of Medical Practice and Research, 2025)
Entering the elderly phase involves various biological, psychological, and social declines. Physical limitations in daily activities and reduced social interactions often trigger mental health issues, particularly depression. This study aims to analyze the relationship between social interaction and independence in Activity of Daily Living (ADL) with the level of depression among the elderly living in social care homes. This quantitative research utilized a cross-sectional study design. The population consisted of elderly residents at the social care home. A sample of 135 respondents was selected using a purposive sampling technique. Data collection instruments included a social interaction questionnaire, the Barthel Index to measure ADL independence, and the Geriatric Depression Scale (GDS-15) to assess depression levels. Data were analyzed using the Spearman Rank correlation test. Results the majority of respondents maintained good social interaction (63.0%) and a high level of independence (85.2%). Most of the elderly did not experience depression (66.7%). Statistical analysis revealed a significant relationship between social interaction and depression (p = 0.000,  r = -0.315), showing a positive correlation where poorer social interaction relates to higher depression scores. Furthermore, a significant relationship was found between ADL independence and depression (p = 0.002, r = -0.267), indicating a negative correlation where higher independence is associated with lower levels of depression. Active social interaction and maintained physical independence contribute significantly to reducing the risk of depression among the elderly in social service environments. It is recommended that social care homes increase group activities and physical rehabilitation programs to sustain the mental well-being of the elderly.